GLYCEMIC AND NON-GLYCEMIC EFFECTS OF EXENATIDE IN PATIENTS WITH DIABETES MELLITUS OF TYPE 2 (DM2) WITH MYOCARDIAL INFARCTION - A. Yu. BABENKO; V. A. ZYKOV; E. N. GRINEVA (Медицинский совет, 2016)
It is known that at DM2 is raised considerably risk of development of myocardial infarction (MI) and mortality from it. For decrease these risk it is important reduction not only glucose level, but also of glycemic variability (GV) and of hypoglycemia (HG). It demands involving of the new drugs in management of glycemia during the acute period of MI, which are capable to provide the decision of these problems and additionally cardioprotection. Glucagon like peptide-1 receptors agonists exenatide) can become possible candidates for it. The purpose of the present research was an estimation of glycemic and non-glycemic exenatide effects in patients with DM2 and MI.